Faktor-Faktor yang Berpengaruh terhadap Kepuasan Pelanggan - Agung Setiawan; Suhaji Suhaji (Jurnal Ilmiah Aset, 2013)
This research aimed to analyze the factors which influence customer’s satisfaction (Study at PT. Superpam Internasional Semarang). The population in this research was all customers at PT. Superpam Internasional Semarang. While the samples in this research were 100 people by using purposive sampling method. The data was obtained by primary data and secondary data. The Data analysis was done by using Regression Analysis. The result of this research indicates that (1) delivery system hadsignificant influence to customer’s satisfaction, thereby hypothesis 1 was received, (2) product quality had significant influence to customer’s satisfaction, thereby hypothesis 2 was received, (3) brand has no significant influence to customer’s satisfaction, thereby hypothesis 3 was refused, (4) price-value relationship had significant influence to customer’s satisfaction, thereby hypothesis 4 was received, (5) employee’s performance had significant influence to customer’s satisfaction, thereby hypothesis 5 wasreceived, and (6) competition had no significant influence to customer’s satisfaction, thereby hypothesis 6 was refused, and employee’s performance, and competition had significant influence together to customer’s satisfaction, thereby hypothesis 7 was received.